The use of 'the eyeball' for topic 'sight' - Aziz, Zahara; Mohd Yusof, Zakiah; Jusoff, Kamaruzaman; Syed Husin, Sharifah Faizah (IDOSI Publications, 2011)
‘Sense of Sight’ and ‘Light and Sight’ are the topics in the chapter ‘Sensory’ for Form 2 Science. An interactive teaching aid call the Eyeball was designed to depict the actual human eye. This article discusses the action research project carried out at Sultan Alauddin Secondary School, Melaka. A total of 21 students from a Form 2 class participated in the research study which was carried out over 8 weeks. The study aims at evaluating the usage of the Eyeball. The data were collected through pre-tests, post-tests, interviews, observations and surveys. Findings indicated that using interactive teaching aids, such as “The Eyeball’ can increase active learning and improve student understanding of the topic. Teachers should diversify their teaching methods to increase learning effectiveness overall.